2022
DOI: 10.1038/s41467-022-35319-w
|View full text |Cite
|
Sign up to set email alerts
|

Spatial transcriptomics landscape of lesions from non-communicable inflammatory skin diseases

Abstract: Abundant heterogeneous immune cells infiltrate lesions in chronic inflammatory diseases and characterization of these cells is needed to distinguish disease-promoting from bystander immune cells. Here, we investigate the landscape of non-communicable inflammatory skin diseases (ncISD) by spatial transcriptomics resulting in a large repository of 62,000 spatially defined human cutaneous transcriptomes from 31 patients. Despite the expected immune cell infiltration, we observe rather low numbers of pathogenic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…Interestingly, we found that IL-17 receptor gene ( IL17RA ) and TNF receptor gene ( TNFRSF1A ) were highly expressed in the epidermis of the PP samples (Fig. 5e ), consistent with the localized cytokine responses identified in keratinocytes 36 .
Fig.
…”
Section: Resultssupporting
confidence: 80%
“…Interestingly, we found that IL-17 receptor gene ( IL17RA ) and TNF receptor gene ( TNFRSF1A ) were highly expressed in the epidermis of the PP samples (Fig. 5e ), consistent with the localized cytokine responses identified in keratinocytes 36 .
Fig.
…”
Section: Resultssupporting
confidence: 80%
“…We next identified all keratinocyte regions immediately adjacent to regions of lymphocytic infiltrate. A published spatial IL-17–induced keratinocyte signature ( 24 ) was quantified in these regions, which revealed activation specifically adjacent to the infiltrate that dampened with increasing spatial distance (Fig. 5B and data file S7).…”
Section: Resultsmentioning
confidence: 99%
“…These cytokine positive spots were associated with sets of immune-related genes associated with pathways such as oxidative stress, neutrophil migration (IL17A, IL17F, IL26), apoptosis (IFNG) and type 2 immunity (IL13, IL4). 30 Numerous studies have been conducted to decipher multiple inflammatory pathways leading to psoriasis. Ding et al utilised ST to identify pathways underlying neutrophilic cell death and neutrophil extracellular traps (NETs), which consist of enzyme and peptides aggregating dead neutrophils.…”
Section: Inflammatory Diseasesmentioning
confidence: 99%
“…Non‐communicable inflammatory diseases (nISD) are diseases classified by altered adaptive immune responses, mostly based on lymphocyte interaction 30 . A recent study, aiming to investigate the inflammatory responder genes underlying adaptive immune responses has applied ST in lesional and non‐lesional skin from patients with psoriasis, atopic dermatitis and lichen planus (LP).…”
Section: Applications In Skin Researchmentioning
confidence: 99%
See 1 more Smart Citation